IIoT and Machine Learning Technology - A case of Investment of TVS Motors Limited (India) - Singh, Netra Pal; Singh, Eesha (Industrija, 2020)
Automobile sector in India is gearing for sharing mobility, electric, smart and connected vehicles. Indian two wheeler makers are either acquiring or investing in IIoT and AI startups to compete in new scenario. This research paper presents brief overview of Indian two wheeler industry and investment /strategies of two wheeler maker TVS Motors Private Limited in the context of future emerging scenario and recent investments in startups. The research paper analyzed TVS recent investment in electric vehicle, shared mobility (renting), IIOT and AI startups. It is concluded that TVS Motors is investing to be at the forefront of electric, smart, shared and connected vehicles. Secondly, to overcome the limitation of internal innovation in new segments in terms of times and lack of knowledge and possible being the first mover in new markets.